Pengembangan E-Modul Kepang dan Pilin Berbasis Canva Pada Mata Pelajaran Pengeritingan Rambut dan Penataan Sanggul Tradisional dan Kreatif - Azlya Firdausi; Nurina Ayuningtyas; Lilis Jubaedah (Journal on Education, 2025)
This research departs from problem of limited time and learning media on hair styling material with braiding and twisting techniques which caused difficulties in the learning process for class XII KKR students at SMK Negeri 7 Tangerang Selatan. The aim of this research is to produce learning media in the form of E-Module Braids and Twist developed based on Canva.This research uses the Research and Development method with a 4-D development model, namely Define, Design, Development, and Disseminate. Data collection in this study used a questionnaire as an assessment of the validation of material and media experts and a practicality test from students. In the material expert assessment I at stage I it was 57.77% and at stage II it was 94.44%. The validation test of the feasibility of the material on material experts 2 was 88.88% with the category "Very Feasible". The results of the validity of the media expert stage I were 80% and stage II 83.63% which "Very Feasible". The results of the product practicality test consisting of individual trials obtained a value of 96.66% and a limited trial of 95.4% wich "Very Practical". Thus, the E-Module Braids and Twist is very feasible and very practical to use as a learning medium.